Motif Etnik (Lampung dan Bali) Pada Tas Kanvas Untuk Kaula Muda - Apriliani, Sari; Utami, Ni Made Purnami; Karja, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
Adding surface designs or paintings to merchandise is one way to increase the value of goods, the value in question is aesthetics and selling price. Agung Bali Collection as the writing partner in the MBKM Entrepreneurial activity, provided knowledge about the massage canting technique which can be used as an additional technique in making surface designs.HOLD ME is a form of Start-Up business that the author created himself, this business is engaged in fashion and art, with canvas bags and endek patchwork as its main products. Endek canvas and patchwork are the main raw materials for making products because the materials are strong and environmentally friendly, as well as the use of endek patchwork in the Agung Bali Collection as a form of preserving traditional culture and patchwork waste processing makes goods have high selling power. Until now, HOLD ME has produced six models of bag products and is planning to expand its business. The product that has been produced is a canvas cloth bag that is collaborated with endek patchwork and has a surface design with a brush technique and massage canting with the use of glitter which can make the bag product unique, beautiful and also special so that consumers do not only enjoy the product through visual beauty but also can be enjoyed from the functional aspect or usability of the product.